2010
DOI: 10.1063/1.3491295
|View full text |Cite
|
Sign up to set email alerts
|

Bragg diffraction using a 100 ps 17.5 keV x-ray backlighter and the Bragg diffraction imager

Abstract: A new diagnostic for measuring Bragg diffraction from a laser-driven crystal using a 100ps 17.5 kV x-ray backlighter source is designed and tested successfully at the Omega EP laser facility on static Mo and Ta single crystal samples using a Mo Ka backlighter. The Bragg Diffraction Imager (BDI) consists of a heavily shielded enclosure and a precisely positioned beam block, attached to the main enclosure by an Aluminum arm. Image plate is used as the x-ray detector. The diffraction lines from Mo and Ta <222> pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In-situ x-ray diffraction was first used to study plasticity in gas gun experiments [1], and was subsequently extended to laser-driven experiments [2][3][4]. Diffraction from single crystals has shown that the material that is initially compressed uniaxially relaxes to a more equiaxed state over a time period that depends on the material.…”
Section: Introductionmentioning
confidence: 99%
“…In-situ x-ray diffraction was first used to study plasticity in gas gun experiments [1], and was subsequently extended to laser-driven experiments [2][3][4]. Diffraction from single crystals has shown that the material that is initially compressed uniaxially relaxes to a more equiaxed state over a time period that depends on the material.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] There are principally two methods for backlit x-ray radiography: area backlighting 13 and Point Projection BackLighting (PPBL). 14,15 For area backlighting, lasers impinging on a high-Z foil generate a source of x rays distributed over the area in which the laser beams hit the target.…”
Section: Introductionmentioning
confidence: 99%